The Influence of the Implementation of the Whole Language Method on the Interests and Conceptual Understanding Ability of Grade III Students of SD Negeri 15 Sungai Gayung Kiri - Sukmawati; Nurmalina; Imam Hanafi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to examine the influence of the Whole Language method on the learning interest and concept understanding ability of third-grade students at SD Negeri 15 Sungai Gayung Kiri. The research uses an experimental design with control and experimental groups. Pretests and posttests are used to measure changes in students' learning interest and concept understanding. The results show that the Whole Language method has a significantly positive impact on both variables. Students in the experimental group demonstrate a higher increase in learning interest and concept understanding compared to the control group. This improvement is evident from the active involvement of students in learning activities and their ability to identify, apply, and generalize the concepts learned. These findings indicate that the Whole Language method is effective in enhancing the quality of language learning and concept understanding in elementary schools.